(untitled) (Zaranie Śląskie, 2024)
At the turn of the last century, the Revd. Stanislaw Tkocz was one of the most important public opinion makers not only in Upper Silesia, but also in Poland. He headed the "Gość Niedzielny" for nearly 30 years (1974-2003). During that time, he was also a close associate of two successive bishops of Katowice – Herbert Bednorz and Damian Zimoń. His voice was greatly valued by both of them, especially with regard to social issues and Church-state relations. He created a new model for a Catholic weekly, which after 1989 was also widely copied by other Catholic media in Poland. In the Third Republic of Poland, he built up independent distribution and proposed an original formula for the magazine, whose main edition was supplemented by diocesan supplements. He created the basis for the further development of the paper, which took place after his death, when Fr Marek Gancarczyk became the head of the weekly. "Gość Niedzielny" is now not only the largest opinion weekly in Poland, but through its regional supplements it is present in twenty dioceses throughout the country